ANALISIS WORK LIFE BALANCE PADA FREELANCER - Devi Ayu Hedianti (Politeknik Negeri Lhokseumawe, 2022)
Abstract: This research has objective to identify the general perspective of person which has role as both freelancer and head of family based on work life balance dimension. This research is applied descriptive method with qualitative approachment. The ways to determine informant is used purposive sampling method consist of key informant, which has role as freelancer and head of family, key informant’s wife, and key informant’s co-workers. Researcher using interview, observation, and documentation for collect the data. Furthermore, researcher using data triangulation to check the validity of the result. The result of this research shows that key informant has not been able to balance himself in terms of WIPL (Work Interference with Personal Life).Keyword: Worl Life Balace, Freelancer